Grocery Shopping before, during and after the Pandemic: A Qualitative Study. (3rd August 2022) - Bridges, Eileen; Fowler, Kendra
Abstract : This research compares grocery shopping attitudes and behaviors before and during the COVID‐19 pandemic, particularly online/offline shopping modes. Prior to COVID‐19, more consumers shopped in person, even if it was not preferred; consumers who preferred to shop online were found to have greater need for control. During the pandemic, more consumers adopted online grocery shopping, and differences in need for control disappeared. Qualitative research suggests that need for control was superseded by lower‐order needs related to food/safety. There is also a growing consumer desire to grocery shop in person, so postpandemic, this is anticipated to increase relative to online shopping.